A search for variable and transient radio sources in the extended Chandra Deep Field South at 5.5 GHz - Bell, M.; Huynh, M.; Hancock, Paul; Murphy, T.; Gaensler, B.; Burlon, D.; Trott, C.; Bannister, K. (2015)
We present a three epoch survey for transient and variables in the extended Chandra Deep Field South at 5.5 GHz with the Australia Telescope Compact Array. A region covering ~0.3 deg2 was observed on time-scales of 2.5 months and 2.5 yr and typical sensitivities 12.1–17.1 μJy beam−1 (1σ) were achieved. This survey represents the deepest search for transient and variable radio sources at 5.5 GHz. In total 124 sources were detected above the 5.5σ level. One highly variable radio source was found with ΔS > 50 per cent implying a surface density of ~3 deg−2. A further three radio sources were found with lower levels of variability equating to a surface density of ~13 deg−2 above a detection threshold of 82.3 μJy. All of the variable sources have inverted radio spectra (between 1.4 and 5.5 GHz) and are associated with active galactic nuclei. We conclude that these variables are young gigahertz peaked-spectrum sources with active and self-absorbed radio jets. We explore the variability completeness of this sample and conclude that the fairly low levels of variability would only be detectable in 3–25 per cent of all sources within the field. No radio transients were detected in this survey and we place an upper limit on the surface density of transient events <7.5 deg−2 above a detection threshold of 68.8 μJy.